Leveraging Artificial Intelligence Technology to Enhance Teacher Performance in Secondary Islamic Schools - Mey Mayangsari; Miftakhul Ilmi Suwignya Putra; Moh Makmun (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study aims to examine how Artificial Intelligence (AI) technology can be utilized to improve teacher performance at MTsN 1 Jombang. This research uses a descriptive qualitative method with the type of field research where the researcher is directly involved in the research location and acts as the primary instrument. Data collection techniques were carried out in observation, documentation, and interviews. There are two data sources in this study, namely primary and secondary. Primary data is generated from interviews with the head of the madrasah, deputy head of curriculum, and six teachers at MTsN 1 Jombang. Simultaneously, secondary data is obtained from books, the internet, and scientific journals. Data analysis in this study went through three stages: data reduction, data presentation, and conclusion drawing. The results of this study show that implementing AI technology to support teacher performance at MTsN 1 Jombang is classified as good. This is reflected in the number of teachers who are helped with administrative tasks, teaching skills, creativity, and learning innovation by utilizing AI technology. Based on the data obtained, at MTsN 1 Jombang, implementing AI technology makes it more accessible. It increases the effectiveness and efficiency in completing various tasks, opening up opportunities for more creative learning innovations.